Manajemen Beban Kerja Guru dalam Meningkatkan Keseimbangan Kerja dan Kehidupan di Madrasah Ibtidaiyah - hidayat, sahrul haj (Maliki Interdisciplinary Journal, 2025)
Teachers play a vital role in improving education, and their performance influences the younger generation. However, excessive workload can reduce teachers' quality of life and negatively impact students. Therefore, teachers need to manage their workload well and maintain their well-being. Workload management includes time planning and task monitoring. A positive work environment and good communication are essential. Regular training can improve the quality of teaching, and maintaining a work-life balance is also important for teachers' mental health. This article uses a peer-reviewed method to explore teacher workload management in Madrasah Ibtidaiyah. The research methodology used is theoretical, allowing researchers to evaluate contributions to current knowledge on the topic. The conclusion obtained in this study is that management is the skill of organizing elements to achieve organizational goals, including planning, organizing, leading, and controlling. In education, teacher workload is regulated by law, and work-life balance is important to reduce stress. Improving the quality of teaching is facilitated by teacher training and principal mentoring. Improving the work-life balance of Madrasah Ibtidaiyah teachers requires efficient workload management. The main focus of madrasah management should be on strategies involving competency development, environmental support, and time management.